REFLEKSI DAN RELEVANSI PEMIKIRAN FILSAFAT HUKUM BAGI PENGEMBANGAN ILMU HUKUM - Junaidi Abdullah (Program Studi Hukum Keluarga Islam, 2015)
Reflection of philosophy of law for legal development by reflecting back to the central questions in the philosophy of law which are based on the aspects epistimologi, ontology, and axiology. The epistemological aspect inquire/study the origin, nature, operational limits of the law. The ontology aspect inquire / learn where the law. The axiology aspect learn the purpose of the law. The relevance of philosophy of law for the development of law by finding links between schools or schools of law with legal developments. Which schools/school of law it plays an important role and influence on legal developments since centuries ago to the present.